Diagnostic performance of 18-leads electrocardiography to distinguish takotsubo syndrome and acute anterior myocardial infarction. (25th November 2020) - Shimizu, M; Cho, S; Hara, K; Ohmori, M; Kaneda, T; Tateishi, R; Yamakami, Y; Shimada, H; Manno, T; Isshiki, A; Kimura, S; Fujii, H; et al.
Abstract: Background: Electrocardiographic (ECG) features on acute phase of Takotsubo syndrome (TTS) is recognized to mimic that of acute anterior myocardial infarction (ant AMI). However, the difference of synthesized 18-leads ECG of both diseases was not elucidated. Purpose: To elucidate diagnostic performance of 18-leads ECG to distinguish TTS and acute anterior AMI. Methods: We firstly enrolled consecutive 40 patients of TTS, and among 500 ant AMI patients, one to two matching was done by their age and gender. Finally, 40+80 patients (74.5±11.2 years, 87 females) were enrolled, and ECG at onset of both group was estimated. Because of multicollinearity, all significant differences were compared by machine learning (Random Forest method). Results: Prevalence of Q wave had no difference. Conversely, ST depression in TTS and ST elevation in ant AMI were significant differences in V7–9 leads. T-wave polarity of V3R-V9 leads were significantly different (flat T-wave in TTS and positive in ant AMI). Machine learning revealed T wave polarity in V7 lead had the highest feature importance. Conclusion: 18-leads ECG at onset had powerful diagnostic performance to distinguish the two diseases. Funding Acknowledgement: Type of funding source: None